A Study on the relationship among member-perceived leadership-style, communication effectiveness, and job satisfaction on selected UP Diliman student organizations - Balgos, Markneel I. (College of Arts and Letters, University of the Philippines Diliman, 2019)
This study aimed to find out the relationship between the member-perceived leadership style and communication style of the leaders, and job satisfaction of the members of selected student organizations in UP Diliman. Leadership style is a pattern of behavior that shows the beliefs and attitudes of leaders towards their members and the organization. Communication effectiveness is the sharing of meaningful and timely information in an empathetic manner between communicators, whether formal or informal. Job satisfaction is the evaluation of an individual to his/her experiences at work as being pleasant or positive, with the organizational environment and work serve as conditioning factors Existing literature showed that the relationship between leadership style and job satisfaction still needs to be explored, and communication effectiveness acted as a mediator of leadership style on performance. Effective communication not only influences group performance, but also the level of group satisfaction. However, the relationship among these variables still need to be explored in local context, particularly in student organizations in UP Diliman. This study aimed to determine the leadership style and communication effectiveness of the leaders, as perceived by their members, determine the job satisfaction of the members, and find the relationship among these variables. The researcher surveyed 80 respondents from eight student organizations that came from four academic clusters: Arts and Letters, Management and Economics, Science and Technology, and Social Sciences and Law. Purposive sampling was used to gather respondents, and a survey questionnaire was used to gather data. The researcher used Avolio and Bass' (2004) Adapted Multifactor Leadership Questionnaire, Sharma and Patterson's (1999) Communication Effectiveness Scale, and Weiss, Dawis, England and Lofquist's (1977) Minnesota Satisfaction Questionnaire (MSQ) to determine the leadership style, job satisfaction in student organizations in UP Diliman. An open-ended question is also asked on the respondents regarding other factors that affect the leadership styles, communication effectiveness, and job satisfaction in student organizations. The Spearman's Rank-Order Correlation Coefficient was the statistical tool used to determine the relationship among the three variables. The results showed that the member-perceived leadership style of the leaders is transformational leadership style, particularly inspirational motivation. The members perceived high communication effectiveness of leaders and also had high job satisfaction. The results showed that at 0.01 level of significance, and with a 0.533 and 1.000 correlation coefficient, there is significant relationship and a strong positive correlation between leadership styles and communication effectiveness of leaders. As leaders exhibit transformational and transactional leadership styles, they become more effective communicators, while as leaders exhibit passive-avoidant leadership styles, they become more effective communicators. The results also showed that at 0.01 level of significance, and with a 0.533 abd 1.000 correlation efficient, there is a significant relationship and a strong positive correlation between the member-perceived communication effectiveness of the leaders and the job satisfaction of the members. As leaders become more effective communicators, members become more satisfied with their work in the organization. Finally, at 0.01 level of significance, and with a 0.593 and 1.000 correlation efficient, there is a significant relationship and a strong positive correlation between the leadership styles and job satisfaction. As leaders exhibit transformational and transactional leadership styles, members most likely to get satisfied with their work in their organizations, while as leaders exhibit passive-avoidant leadership styles, members are most likely to get dissatisfied with their work in their organizations.